2020
DOI: 10.1371/journal.pone.0227238
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlates of sarcopenia and falls in Parkinson’s disease

Abstract: BackgroundSarcopenia is a complex and multifactorial geriatric condition seen in several chronic degenerative diseases. This study aimed to screen for sarcopenia and fall risk in a sample of Parkinson's disease (PD) patients and to investigate demographic and clinical factors associated. MethodsThis is a cross-sectional study. We evaluated 218 PD patients at the Movement Disorders Clinic in Fortaleza, Brazil, and collected clinical data including experiencing falls in the six months prior to their medical visi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 37 publications
0
33
1
1
Order By: Relevance
“…One study found that higher fat infiltrations were detected in the psoas and thigh muscles in female PD patients compared with female healthy controls (17). Another study found that female sex was independently associated with sarcopenia (16). The current meta-analysis did not find a difference in both male and female sex ratios between PD with and without sarcopenia.…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…One study found that higher fat infiltrations were detected in the psoas and thigh muscles in female PD patients compared with female healthy controls (17). Another study found that female sex was independently associated with sarcopenia (16). The current meta-analysis did not find a difference in both male and female sex ratios between PD with and without sarcopenia.…”
Section: Discussioncontrasting
confidence: 57%
“…Another study found that older healthy controls and PD participants had significantly decreased CMC and electromyography (EMG) power at low beta frequencies (13-21 Hz) compared with young healthy controls, whereas there was no difference between the older healthy and PD groups (37). Additionally, one study found that PD participants had significantly decreased beta frequencies (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) for tibialis anterior muscle compared with older healthy controls, whereas there was no difference in the magnitude of CMC between older and younger healthy controls (38). This might hint toward one of the potential features underpinning gait speed changes and risk of falling in PD patients with sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations